Exploring the potential of myo-inositol in thyroid disease management: focus on thyroid cancer diagnosis and therapy - Razavi, S. Adeleh; Kalari, Mohadeseh; Haghzad, Tahereh; Haddadi, Fatemeh; Nasiri, Shirzad; Hedayati, Mehdi (Frontiers in Endocrinology, 2024)
Thyroid cancer (TC) is a malignancy that is increasing in prevalence on a global scale, necessitating the development of innovative approaches for both diagnosis and treatment. Myo-inositol (MI) plays a crucial role in a wide range of physiological and pathological functions within human cells. To date, studies have investigated the function of MI in thyroid physiology as well as its potential therapeutic benefits for hypothyroidism and autoimmune thyroiditis. However, research in the field of TC is very restricted. Metabolomics studies have highlighted the promising diagnostic capabilities of MI, recognizing it as a metabolic biomarker for identifying thyroid tumors. Furthermore, MI can influence therapeutic characteristics by modulating key cellular pathways involved in TC. This review evaluates the potential application of MI as a naturally occurring compound in the management of thyroid diseases, including hypothyroidism, autoimmune thyroiditis, and especially TC. The limited number of studies conducted in the field of TC emphasizes the critical need for future research to comprehend the multifaceted role of MI in TC. A significant amount of research and clinical trials is necessary to understand the role of MI in the pathology of TC, its diagnostic and therapeutic potential, and to pave the way for personalized medicine strategies in managing this intricate disease.